Good living, solidarity economies, and public universities in Peru - Montoya Canchis, Luis (Cooperativismo & Desarrollo, 2016)
Purpose: This paper presents the experience of the Social, Solidarity, and Popular Economies Seminar at the Universidad Nacional Mayor de San Marcos in Peru. Description: Taking up the challenge of reshaping universities and imagining new university programs of action demands that we question the imposition of the Eurocentric structure of knowledge. This is necessary in order to promote its decolonization and, therefore, encourage dialogue between scientific and humanistic knowledge, as well as with lay, popular, traditional, and urban knowl edge from non-Western cultures. Viewpoint: An attempt is made to overcome the academic division of disciplines in order to propose an inter- and transdisciplinary structuring. This structuring will then make professional training,research aimed at meeting the demands of capitalist society, and the necessary public administration give way to another one oriented toward good living,solidarity economies, and the socialization and decolonization of knowledge, in addition to the power relations that pose a great challenge. Conclusions:This review is in tended to develop a dialogue of knowledges about the social, solidarity, popular, and community economies, as well as experiences of intervention and advocacy processes at the university level.